Survey on Reliable Routing in Wireless Networks (International Journal of Advanced Research in Science, Management and Technology, 2021)
Opportunistic networks are one of the most interesting evolutions of MANETs. In opportunistic networks, route connecting to the mobile nodes never exits, mobile nodes communicate with each other when they got opportunity to communicate. Furthermore, nodes are not supposed to possess or acquire any knowledge about the network topology. Routes are built dynamically, while messages are route between the source and the destination, and any possible node can opportunistically be used as next hop, provided it is likely to bring the message closer to the final destination. These requirements make opportunistic networks a challenging and promising research field. In this paper we describe composite approach for routing in opportunistic networks, rendering traditional routing protocols unable to deliver messages between hosts. Thus, there is a need for a way to route through such networks. We propose composite approach which combines Epidemic Routing and Probabilistic Routing approaches together.
Keywords: Epidemic Routing, Routing Opportunistic networks, Probabilistic Routing.